Microencapsulation of Essential Oils and Oleoresins: Applications in Food Products - Beatriz Fernandes; M. Conceição Oliveira; Ana C. Marques; Rui Galhano dos Santos; Carmo Serrano (Foods)
Essential oils (EOs) and oleoresins (ORs) are plant-derived extracts that contain both volatile and non-volatile compounds used for flavoring, coloring, and preservation. In the food industry, they are increasingly used to replace synthetic additives, aligning with consumer demand for natural ingredients, by substituting artificial flavors, colorants, and preservatives. Microcapsules can be added to a vast range of foods and beverages, including bakery products, candies, meat products, and sauces, as well as active food packages. However, incorporating EOs and ORs into foods and beverages can be difficult due to their hydrophobic nature and poor stability when exposed to light, oxygen, moisture, and temperature. Microencapsulation techniques address these challenges by enhancing their stability during storage, protecting sensitive molecules from reacting in the food matrix, providing controlled release of the core ingredient, and improving dispersion in the medium. There is a lack of articles that research, develop, and optimize formulations of microencapsulated EOs and ORs to be incorporated into food products. Microencapsulated ORs are overlooked by the food industry, whilst presenting great potential as natural and more stable alternatives to synthetic flavors, colorants, and preservatives than the pure extract. This review explores the more common microencapsulation methods of EOs and ORs employed in the food industry, with spray drying being the most widely used at an industrial scale. New emerging techniques are explored, with a special focus on spray drying-based technologies. Categories of wall materials and encapsulated ingredients are presented, and their applications in the food and beverage industry are listed.